The nature of association of oral para-functional habits with anxiety and big-five personality traits in Saudi adult population - Nouf Albesher; Modi Aljohani; Misam Alsenani; Ohood Turkistani; Mahmoud Salam; Adel Almutairi (Saudi Dental Journal)
Objective: The aim of this study was to determine the prevalence of various types of oral parafunctional habits and evaluate its association with the level of anxiety and personality traits among the Saudi adult population. Material and methods: It is a cross-sectional study based on an anonymous, Arabic language electronic survey distributed through social media networks among Saudi public community. Eligible cases were 1403. Study participants were Saudi adults who practiced at least one of the five oral parafunctional habits (Nail biting, Grinding, Clenching, Lip/object biting, and daily gum chewing). Level of anxiety was measured using Hamilton Anxiety Scale. The Big Five personality traits were evaluated using the Ten-Item Personality Inventory (TIPI) scale. Descriptive statistics (n,%; Mean ± SD), bivariate analytic statistics (Pearson’s Chi square, T-test) and binary logistic regression analyses were conducted to determine factors associated with the study outcomes. Results: The most common reported parafunctional habit was daily gum chewing (86%), followed by lip/object biting (59%). Mild anxiety symptoms were prevalent in 84% of sample. However, very severe anxiety was prevalent in only 2%. The leading personality trait was conscientiousness while extraversion trait had the least mean. A significantly positive relationship was observed between the severity of anxiety levels and most oral parafunctional habits. Conscientiousness and emotional stability traits were significantly related to all oral parafunctional habits. However, extraversion and openness to experience were not significantly associated with any parafunctional habit. Conclusions: Oral parafunctions showed in this study a high prevalence and were significantly associated with higher anxiety levels and to conscientiousness and emotional stability personality traits.